Thermodynamic Efficiency of an Advanced 4th Generation VHTR Propulsion Engine for Large Container Ships - Głuch Jerzy; Kodlewicz Tomasz; Drosińska-Komor Marta; Ziółkowska Natalia; Breńkacz Łukasz; Ziółkowski Paweł (Polish Maritime Research)
In response to global initiatives to reduce greenhouse gas emissions, the maritime industry must adopt green propulsion solutions. This paper analyses the operational potential of very high-temperature reactors (VHTRs) as an innovative propulsion source for large container ships. Calculations are carried out for ships produced between 2018 and 2020 with a capacity of more than 20,000 TEU. For these ships, the average power of the main system is calculated at around 64.00 kW. The study focuses on a propulsion engine system with features such as extraction control, bypass control, and either one or two turbines. The direct thermodynamic cycle of the VHTR offers high efficiency, smaller sizes, and flexible power control, thus eliminating the need for helium storage and enabling rapid power changes. In addition, this article highlights the advantages of bypass control of the turbine, which avoids the need to shut down the propulsion engine in the harbour. The findings suggest that nuclear propulsion could play a crucial role in the future of maritime technology.